2018
DOI: 10.1542/hpeds.2018-0009
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Parental Tobacco Dependence Treatment Among a Children’s Hospital Staff

Abstract: A B S T R A C TOBJECTIVES: To assess employee support for and knowledge of smoking cessation programs for patients' parents and staff and employees' level of comfort discussing smoking with patients and their families before and during a hospital-wide study of a tobacco cessation and/or exposure reduction program for inpatients' parents who smoke. METHODS:Clinical staff were invited to complete online surveys at the beginning of and 19 months into a randomized controlled trial to test the efficacy of an inpati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 16 publications
(9 reference statements)
0
12
0
Order By: Relevance
“…Although rates of smoking cessation counseling in pediatric primary care settings are increasing, rates of recommending or prescribing pharmacological cessation therapy remain low at 15% and 3%, respectively 5 . Reasons for low prescription rates by pediatric providers include concerns about lack of knowledge and scope of practice, due to feeling uncomfortable in prescribing medications for parents who are not their patients 5 - 7 . Nevertheless, the American Academy of Pediatrics strongly encourages pediatric practitioners to prescribe pharmacological cessation medications in conjunction with counseling during children's healthcare visits to help parents quit smoking 2 , 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Although rates of smoking cessation counseling in pediatric primary care settings are increasing, rates of recommending or prescribing pharmacological cessation therapy remain low at 15% and 3%, respectively 5 . Reasons for low prescription rates by pediatric providers include concerns about lack of knowledge and scope of practice, due to feeling uncomfortable in prescribing medications for parents who are not their patients 5 - 7 . Nevertheless, the American Academy of Pediatrics strongly encourages pediatric practitioners to prescribe pharmacological cessation medications in conjunction with counseling during children's healthcare visits to help parents quit smoking 2 , 3 .…”
Section: Introductionmentioning
confidence: 99%
“…6 Caregivers are generally receptive to tobacco cessation programs during their child' s hospitalization. 6,8 To our knowledge, authors of only one study have investigated the perspectives of pediatric inpatient staff (eg, physicians, physician trainees, nurses, respiratory therapists) on tobacco cessation programs for caregivers. Although preliminary support for such programs was indicated in the study, 8 to date, the pediatric hospital remains underused for provision of this evidencebased care, and barriers remain poorly understood.…”
mentioning
confidence: 99%
“…Further, prior studies have demonstrated both the feasibility and the effectiveness of smoking cessation interventions in hospitalized children. [27][28][29][30] Unfortunately, however, SHS exposure is often not documented at the time of hospitalization, and many opportunities to intervene are missed. 25,31 Thus, there is a need for improved strategies to reliably identify and intervene on SHS-exposed children in the hospital setting.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to scores representing baseline health, admission scores were lower across all four conditions for SHS-exposed children. Only children with croup, however, had (22) 559 (24) 316 (14) 663 42304 (19) 402 (26) 206 (13) 249 (34) 207 (29) 157 (22) 110 ( 740 (32) 342 (15) 563 (24) 415 (26) 502 (32) 255 (16) 409 (26) 249 (34) 238 (33) 87 (12) 154 (21 714 (31) 423 (18) 156 (10) 645 (41) 482 (30) 298 (19) 84 (12) 287 (39) 232 (32) 125 (17) .6 a Comorbidities were assessed using the Pediatric Medical Complexity Algorithm (see reference 10); Pediatric Respiratory Illness Measurement System eligibility criteria excluded children with immunodeficiency, cystic fibrosis, a history of prematurity <32 weeks, chronic neuromuscular disease, cardiovascular disease, pulmonary diseases (other than asthma), and moderate to severe developmental delay. Data are presented as no.…”
Section: Home Shs Exposure and Health-related Quality Of Lifementioning
confidence: 99%